Sulfonic acid functionalized porous organic polymer as a heterogeneous catalyst for efficient pseudo four-component synthesis of dihydro-2-oxypyrroles - Saba Daliran; Seyedeh Fatemeh Hosseini; Ali Reza Oveisi; Esmael Sanchooli; Enrique Rodríguez-Castellón; Daniel Ballesteros-Plata (BMC Chemistry)
Abstract Background A new sulfonated porous organic polymer (POP-SO3H) is synthesized through post-synthetic modification of (PSM) of the COF-366 through a two-step process: first, transformation of imine (C = N) functional groups into amine (C-N) linkages, followed by treatment of the amine groups with 1,3-propane sultone. Then, it was used for the first time as an efficient heterogeneous catalyst for the preparation of dihydro-2-oxo pyrroles under mild conditions. Results The nominal solid was characterized and confirmed by a variety of techniques such as FT-IR, PXRD, SEM/EDX, UV-Vis DRS, XPS, HRTEM, BET surface area and TGA/DSC. The catalytic performance of POP-SO3H was assessed and optimized in the pseudo four-component synthesis of dihydro-2-oxopyrroles. Accordingly, the optimal conditions were found to be 20 mg of POP-SO3H in methanol at room temperature for 1 h, giving the highest product yield of 92% of the desired product. Conclusion The above procedure demonstrated remarkable advantages such as high product yields, operational simplicity, short reaction times, and excellent catalyst reusability (four consecutive cycles without significant loss of activity). The catalyst showed superior performance compared to the pristine COF and many existing systems, operating efficiently at room temperature with a relatively low catalyst loading.